2021
DOI: 10.21037/qims-20-860
|View full text |Cite
|
Sign up to set email alerts
|

Pericoronary adipose tissue attenuation assessed by dual-layer spectral detector computed tomography is a sensitive imaging marker of high-risk plaques

Abstract: Background: The pericoronary fat attenuation index (FAI) derived from conventional polychromatic computed tomography (CT) can capture the presence of coronary inflammation. However, conventional polychromatic CT has limitations in material component differentiation, and spectral CT could have a better ability to discriminate tissue characteristics. Hence, this study sought to assess pericoronary adipose tissue (PCAT) attenuation using spectral CT and explore its association with atherosclerotic plaque characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 27 publications
4
14
0
Order By: Relevance
“…This study showed that the FAI obtained by single-energy reconstruction at the low-energy end of the spectrum (40 keV) could better distinguish changes in the PCAT density. This result is consistent with the results of Rodriguez-Granillo et al [24] and our team [19,20]. We also observed similarities between λ HU and FAI 40keV , which may be a marker that re ects the in ammatory state of PCAT when the TyG index is elevated.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This study showed that the FAI obtained by single-energy reconstruction at the low-energy end of the spectrum (40 keV) could better distinguish changes in the PCAT density. This result is consistent with the results of Rodriguez-Granillo et al [24] and our team [19,20]. We also observed similarities between λ HU and FAI 40keV , which may be a marker that re ects the in ammatory state of PCAT when the TyG index is elevated.…”
Section: Discussionsupporting
confidence: 93%
“…These results may help explain the mechanisms related to plaque progression and instability in patients with insulin resistance.Recently, a study demonstrated that double-layer spectral detector computed tomography (SDCT) is suitable for coronary CTAs [15], especially using virtual monochromatic imaging (VMI) reconstruction at a low-energy level (40 keV), which signi cantly increases the contrast of soft tissue [16,17,18]. Moreover, other studies have shown that SDCT is more sensitive and accurate for quantifying pericoronary adipose tissue (PCAT) than conventional computed tomography (CT) [19,20]. Therefore, we hypothesized that the PCAT index assessed by SDCT might be more helpful for distinguishing PCAT in ammation in patients with IR.Thus, we investigated associations between the pericoronary FAI and plaque features derived from SDCT and the serum TyG index level in patients to explore the possible mechanisms by which the TyG index affects coronary artery in ammation and plaque progression in IR.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This may suggest that PCAT surrounding the atherosclerotic plaques with non-calcified component has higher metabolically activity. This may be related to the characteristic of highly inflamed atherosclerotic plaque, which has been discussed in detail in another separate work of our research team ( 39 ). Interestingly, the opposite results were obtained in non-CAD cases, which showed that FAI 40keV adjacent to non-calcified plaques was the lowest, although the differences between the groups were not statistically significant.…”
Section: Discussionmentioning
confidence: 81%
“…There is increasing evidence, that EATA is modulated by several factors, not only the regulation of brown adipose tissue-like features, but also local in ammation around the coronary arteries, i.e. in the pericoronary adipose tissue (PCAT) [41][42][43] . Augmented cellularity due to in ammation or an increase in extracellular matrix in brotic (post)in ammatory conditions 29 can increase EATA.…”
Section: Eata Gradually Decreases the Of Changes In Glucose Metabolismmentioning
confidence: 99%